FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS USAHA TANI DAN KEBERHASILAN PROGRAM SIMANTRI DI KABUPATEN KLUNGKUNG - Dewi, Ni Luh Putu Rossita; Utama, Made Suyana; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.02.TAHUN 2017, 2017)
Agricultural development occurs when efforts to optimize the use of natural resources and appropriate technology . Government attention in agricultural development, demonstrated through Integrated Farming Systems Program ( Simantri ) . Simantri Program is a program to increase the number of farm production which might be expected to have an impact on the increase in income and welfare of farmers . The data in this research is the analysis of structural equation with alternative Partial Least Square ( PLS ) . The evaluation results indicate that the goodness of fit of the structural model to get the value of Q 2 in this research model of 0.873 means that the information contained in the data 84.2 percent can be explained by a model that is the characteristic variables farmers, social capital , productivity of farming and Simantri program success , while the remaining 15.8 percent is explained by other variables not included in the model.   Keywords : Productivity, the success of the program, Program Simantri
Keywords: Productivity, the success of the program, Program Simantri